1999
DOI: 10.1103/physrevb.60.16350
|View full text |Cite|
|
Sign up to set email alerts
|

Orbital-free kinetic-energy density functionals with a density-dependent kernel

Abstract: We report linear-response kinetic-energy density functionals, which show significant improvement over the Wang-Teter, Perrot, Smargiassi-Madden, Wang-Govind-Carter functionals, yet still maintain O(N ln N) scaling. Numerical tests show that these functionals, which contain a double-density-dependent kernel, can reproduce the Kohn-Sham results almost exactly for several aluminum bulk phases. We further show that with a sensible choice of the uniform background density, energies of formation for the low-index al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
415
0
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 250 publications
(420 citation statements)
references
References 54 publications
4
415
0
1
Order By: Relevance
“…For other systems we found a smaller but significant reduction (e.g., 2 SCF steps are saved on average out of 10 for (H 2 O) 64 ).…”
Section: Guiding the Scf To Convergence: An Additional Diis Layermentioning
confidence: 79%
See 2 more Smart Citations
“…For other systems we found a smaller but significant reduction (e.g., 2 SCF steps are saved on average out of 10 for (H 2 O) 64 ).…”
Section: Guiding the Scf To Convergence: An Additional Diis Layermentioning
confidence: 79%
“…For (H 2 O) 64 , we have assessed the DIIS on 10 AIMD steps and found that DIIS on All 256 subsystems were computed at the C-point. eQE 1 : Fully optimized eQE employing subsystem specific basis sets, and calculating the GGA xc and kinetic potentials of the total density only once on the supersystem cell utilizing the large_comm communicator (i.e., "fancy parallelization").…”
Section: Molecular Periodic Systems (Liquids and Crystals)mentioning
confidence: 99%
See 1 more Smart Citation
“…λ = 1 is the Weizsacker correction and is suitable for rapidly varying electron densities, λ = 1/9 gives the conventional gradient approximation and is suitable for slowly varying electron densities, λ = 1/6 effectively includes the 4th order effects and λ = 0.186 was determined from analysis of large atomic-number limit of atoms. This class of functionals makes computations of large and complex systems tractable, though it does have limitations and improvements have been proposed (Wang et al, 1998(Wang et al, , 1999Smargiassi & Madden, 1994;Wang & Teter, 1992). We confine our attention to the Thomas-Fermi-Weizsacker family of functionals (2) for now for clarity.…”
Section: Formulationmentioning
confidence: 99%
“…In the body of the paper, we confine ourselves to the Thomas-Fermi-Weizsacker kinetic energy functional (Parr & Yang, 1989;Thomas, 1927;Fermi, 1927) for clarity. However, we show in the Appendix how our approach can be extended to the more recent and accurate kernel kinetic energy functionals (Wang et al, 1998(Wang et al, , 1999Smargiassi & Madden, 1994;Wang & Teter, 1992). …”
Section: Introductionmentioning
confidence: 99%